The Effectiveness of Learning English Online among Second-Year Engineering Undergraduates - Palpanadan, Sarala Thulasi; Ahmad Zuki, Ros Eliana; Adnan, Muhammad Nor Fazari (Development in Language Studies, 2023)
English language proficiency is a crucial skill for students worldwide, as it opens doors to global opportunities and facilitates effective communication in various fields. In Malaysia, English is taught as a second language and is widely used for academic and professional purposes. However, concerns have arisen about the deterioration of English language proficiency among Malaysian undergraduates, particularly among those pursuing degrees in engineering. This study was conducted to investigate the challenges faced by university students to study English online. The data were collected from a group of second-year students from an engineering course in a public university in Malaysia. Data was analyzed descriptively. It was found that the majority of the students enjoyed learning English online even though they preferred face-to-face learning. This study provides some suggestions for the challenges faced by students including the use of preferred online platforms such as ‘Author’, having support from family and friends, and sustaining strong mental health for an effective online learning environment.